The impact of material management on construction projects performance / Mahadi Fazlin and Norazura Mizal Azzmi - Fazlin, Mahadi; Mizal Azzmi, Norazura (2023)
The Malaysian construction sector is crucial for the nation's economy, but inadequate materials management has led to project underperformance. This research paper investigates the impact of material management on construction project performance and identifies strategies for efficient management. The study uses qualitative analysis, interviews, observations, and literature reviews to analyse case studies of two construction projects, LUMINA Taman Harmonis (A) and LILIUM Puncak Iskandar (B). The findings highlight the importance of proper material management practices, including planning, confirmation, negotiation, and supplier engagement. Effective material management significantly impacts project performance, reducing costs, minimizing waste, and enhancing efficiency. Recommendations for the Malaysian construction industry include fostering collaboration among stakeholders, integrating data analytics, and embracing technology-driven solutions. The study also suggests future research directions towards sustainable material selection and eco-friendly construction practices to strengthen the sector's competitiveness and align with national development objectives.